Phase transformation of kaolinite clay - Chakraborty, Akshoy Kumar (Springer India, 2014)
The book depicts comprehensive studies on thermal decomposition of Kaolinite by different physico-chemical methods carried out by various scientists in last 100 years and results of the studies conducted by author in past 33 years. It also provides a critical analysis of different views on Kaolinite-Mullite reaction series, characterization of controversial spinel phase in Kaolinite-Mullite reaction series and explanation of DTA events of Kaolinite. The book helps both researchers and students to realise the new mechanism of transformation of Kaolinite to Mullite. The new reaction processes discussed in the book also helps ceramic experts to synthesize Mullite grains in commercial way for production of Mullite porcelain and Mullite refractory.